NMR characterization of dilauroyl phosphatidylcholine in adsorbed monolayers at fluid interfaces studied by multiscale computations. Issue 19 (8th July 2016) - Tsoneva, Yana; Tadjer, Alia; Mineva, Tzonka
Abstract: Structural characteristics of model monolayers of dilauroyl phosphatidylcholine (1, 2‐dilauroyl‐sn‐glycerol‐3‐phosphatidylcholine [DLPC]) adsorbed at the water/vapors and water/octane interfaces were studied by means of computational chemistry methods. Coarse‐grained, followed by all‐atom molecular dynamics simulations were used to obtain the monolayers equilibrium structures at room temperature at both fluid interfaces. The analysis of the polar head orientation, polar region thickness, tail lengths, and NMR order parameter revealed that the different interface composition affects only the tail lengths and their orientation with respect to the interface. At the octane/water boundary the DLPC tails are less extended than the tails at the water/vacuum interface and are rather significantly tilted or multiply folded. Very similar structuring of the polar DLPC region at both studied boundaries was established. Dynamic 13 C NMR chemical shift values, δ ( 13 C) computed with density functional theory allowed to identify the interface effect on the DLPC molecular structure and the intramolecular motions in the adsorbed monolayer at the room temperature equilibrium. Detailed analysis of these dynamic δ ( 13 C) values compared with available experimental data and static δ ( 13 C) estimates of one DLPC low‐energy conformer are presented and discussed. Abstract : Phospholipids are amphiphilic molecules, which can be obtained from natural products (egg yolk, soybeans, etc.). At the oil/water interface, they are known to act as very good stabilizers of emulsion structures. NMR deuterium order parameter and dynamically averaged 13 C NMR chemical shifts are used to relate the intermolecular structuring of a model lipid monolayer at water/vapors and water/oil interfaces with the intramolecular bonds and angles fluctuations.